Factor VIII as a marker of endothelial cells in follicular carcinoma of the thyroid. Issue 9 (September 1983) - Harach, H R; Jasani, B; Williams, E D
Abstract : Factor VIII-related antigen is a recognised marker of endothelial cells. A brief immunocytochemical study of its distribution in follicular carcinoma of the thyroid and its value in the recognition of vascular invasion by this tumour has been carried out. Ten cases of follicular carcinoma of the thyroid were studied. In each strong endothelial staining was found in the majority of vessels in the adjacent normal thyroid. Lymphatic endothelium was negative. In eight of the 10 cases the staining of vessels within the tumour was absent or very weak. Staining was also absent in the majority of vessels completely occluded by tumour, but was present in the endothelium of vessels only partly occluded by tumour. It is concluded that factor VIII-related antigen staining has only limited value in the recognition of vascular invasion in follicular carcinoma. The absence of vascular staining in the tumour leads us to suggest that inhibition of factor VIII production by the tumour could be a possible mechanism which facilitates vascular invasion and metastasis.